From the unified games of the special olympics to the inclusive games of the future - Babicheva A.E.; Frolova E.V. (Theory and Practice of Physical Culture, 2023)
Digital sport promotes inclusion and the creation of equal opportunities for all participants. This sports digital technology will help people with disabilities develop psychophysical conditions, form teamwork skills, improve concentration and make decisions in rapidly changing situations.